Samodzielność finansowa polskich samorządów na tle krajów Unii Europejskiej - Alińska, Agnieszka (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2006)
The present tendencies in the scope of financial management within local governments both in Poland and in most EU countries show aspirations for systematic increase of the financial autonomy level of local governments. This results from, among other things, the fact that the traditional range of the freedom of dealing with income among local governments is directly influenced by the share level of the own income within the total one. Gaining the appropriate own income allows realizing the tasks and responsibilities that according to the valid law regulations have been transferred to local governments in EU countries, and that simultaneously take the priority importance in the social and economic development of the region. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1148, s. 263-272